Analysing oily wastes in soils - Coulon, Frederic (Institution of Chemical Engineers, 2009)
Many hydrocarbon contaminated sites posing potential risks to human health harbour weathered, ‘mid-distillate' or heavy oils. Now, a bioremediation consortium (PROMISE), led by Cranfield University, has developed a novel and robust analytical procedure for weathered hydrocarbon contaminated soils within a UK risk-based framewo